Alice in Wonderland: «Art exists because reality is neither real nor significant» (Itinera, 2023)
What are the contaminations between art and architecture in today’s world? In the relationship with the architectural and urban space, what role does art play whenever art and architecture come into contact? Quoting James Ballard, the title of the present essay represents a sort of provocation, especially in case of association with Canaletto’s famed Capriccio palladiano and to the in some ways inappropriate usage that Aldo Rossi made of it. Starting from the observation that the composition made by Canaletto is, in a certain way, truer than Venice itself, one might wonder about the role of art in the construction of the architectural and urban image and, through some examples, affirm that in the present time art is a kind of seismograph that pushes architects to look beyond, to investigate the field of the unspoken or the unthinkable and it is used, in many cases, as a device to substantiate architecture itself and its outcomes.How and through which instruments? The answer lies in the works as mere instruments used to go back to the (implicit or explicit) canons and codes used, or perhaps to get to admit that, conversely, they often fade into a hermeneutic of the indeterminate, in relation to which identifying limits and boundaries seems increasingly difficult.Who makes what, between art and architecture? Ballard explains it masterfully and some artists show it clearly. The whole complex of these experiences is bound to the (solid) architecture and its theoretical corpus together with the desire to reflect on processes, procedures, transcriptions, and metamorphoses capable of feeding architecture and its languages.